The waiting room: memory and identity: a theatrical exploration of identity through memory - Henriques, Leila (My University, 2016)
This thesis, subtitled Memory and Identity: A theatrical exploration of identity through memory, uses theatre as an investigative tool and unpacks the idea that we are connected to each other through three different forms of memory and knowledge; namely personal knowledge, family knowledge and genetic knowledge. This written component forms part of a practice-based research performance project. The practice-based research uses playmaking to draw on these three memory forms and explores the interpersonal relationships of a life lived in Johannesburg, South Africa, in 2009. Each knowledge form has been explored: personal knowledge draws on my personal lived experience as a South African citizen and also as a theatre practitioner from 1992 to 2009; family knowledge draws on stories handed down in my family and an exploration into my family dynamics through body memory; and genetic knowledge uses the Portuguese song form of Fados as a way of accessing, formalising and recreating the narrative I tell. I have used theatre to explore the links between myself and my personal memories, communal family memories and genetic memories. I have explored the relationship between memories of a personal lived experience in Johannesburg in the 1970s and my own social positioning in Johannesburg in 2009 (the year my mother died). I found ways in which old patterns of behaviour were repeated under entirely different circumstances - and through the practice of making the play how these patterns could be disrupted - and new pathways for knowing and forming an identity could be formed. In this research document I have elaborated on the three basic stages of my investigation: research into personal, family and genetic memory; my play-making practice; and finally how the process of making and performing the play shifted my ideas about myself, my family and, more subliminally, my place in South Africa - in the past, present and future. My finding is that while memory - in all its different forms - has a key role in shaping identity, identity is a distinct and ever-evolving entity that defies time and place and conditioning. There is a point at which what is given to us is left behind and we are able to imagine alternatives for ourselves that we can grow towards and claim as our own.
A research report submitted in fulfilment of the requirement for the degree Master of Arts in Dramatic Art to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2016
Keywords: Interpersonal relations